(untitled) - Lane, Henry W. (Chichester, West Sussex, United Kingdom, 2014)
This is the seventh edition of International Management Behavior , an established text for students and executives developing the knowledge, perspective and skills required for leading and managing people in global business.
Keywords: Organizational behavior,Hành vi tổ chức